Mortality and feeding preference of Nezara viridula and Piezodorus guildinii (Hemiptera: Pentatomidae) fed on pods and immature soybean seedss - Panizzi, Antônio R. (Pesquisa Agropecuaria Brasileira, 2014)
Nymphs of the southern green stink bug, Nezara viridula (L.), and of the small stink bug, Piezodorus guildinii (Westwood), consistently showed higher mortality when fed on immature soybean seeds as compared to green soybean pods. Nymphs and adults of N. viridula preferred pods to immature soybean seeds. Additional studies are needed to identify the cause(s) of the differential mortality and feeding preferences showed by the stink bugs on these two foods.